Complicated Intubations are Associated with Bronchopulmonary Dysplasia in Very Low Birth Weight Infants - Glenn, Tara; Fischer, Linnea; Markowski, Ashley; Carr, Cara Beth; Malay, Sindhoosha; Hibbs, Anna Maria (American Journal of Perinatology, 2021)
Objective This study aimed to evaluate the association between desaturation <60% (severe desaturation) during intubation and a total number of intubation attempts in the first week of life in very low birth weight (VLBW) infants with adverse long-term outcomes including bronchopulmonary dysplasia (BPD) and severe periventricular/intraventricular hemorrhage grade 3 or 4 (PIVH).Study Design A retrospective chart review was performed on VLBW infants intubated in the neonatal intensive care unit during the first week of life between January 2017 and July 2020. Descriptive tables were generated for two outcomes including BPD and PIVH. Multivariable logistic regression was performed for each outcome including significant predictors that differed between groups with a p-value of <0.2.Results A total of 146 patients were included. Patients with BPD or PIVH had a lower gestational age, and patients with BPD had a lower BW. Patients with BPD had a greater number of intubation attempts in the first week of life (4 vs. 3, p < 0.001). In multivariable logistic regression controlling for confounding variables, the odds developing BPD were higher for patients with increased cumulative number of intubation attempts in the first week of life (odds ratio [OR]: 1.29, 95% confidence interval [CI]: 1.03–1.62, p = 0.029). Post hoc analyses revealed increased odds of developing BPD with increased number of intubation encounters in the first week of life (OR: 2.20, 95% CI: 1.04–4.82, p = 0.043). In this post hoc analysis including intubation encounters in the model; desaturation <60% during intubation in the first week of life was associated with increased odds of developing BPD (OR: 2.35, 95% CI: 1.02–5.63, p = 0.048).Conclusion The odds of developing BPD for VLBW infants were higher with increased intubation attempts and intubation encounters. In a post hoc analysis, the odds of developing BPD were also higher with desaturation during intubation. Further research is needed to determine mechanisms of the relationship between complicated intubations and the development of BPD.Key Points
Keywords: neonatal endotracheal intubation; intubation complications; adverse events; patient safety; bronchopulmonary dysplasia; periventricular-intraventricular hemorrhage; very low birth weight infants